OPTIMALISASI PELAKSANAAN PROGRAM JAMINAN KESEHATAN NASIONAL MELALUI PENINGKATAN DAN PENGUATAN LAYANAN FASILITAS KESEHATAN PRIMER DENGAN PENDEKATAN GATE KEEPER IN MANAGED CARE DALAM RANGKA PENCAPAIAN UNIVERSAL HEALTH COVERAGE DI KOTA MALANG - Aristanto, Eko; Ratnaningsih, Christina Sri; Handayani, Krisnawuri (Jurnal Manajemen dan Kewirausahaan, 2016)
As the site of the first level of health care, Puskesmas has a role that is essential for the success of JKN in Indonesia. Therefore, the success of JKN largely determined by Puskesmas, in particular towards healing a patient that can covered in Puskesmas, which do not need to get a reference to the hospital (Rumah Sakit). The main purpose of this study is : the first, identify the availability of medical and non-medical personnel at the primary level health facility, identify the characteristics of the national healthcare services at the primary level health facility, identify the conditions of the existance health service of facilities and infrastructure at the primary level health facilities. Second, identify procedure and delivery system capital funding on the primary level health facility, identify the constraints and barriers to health services at the primary level health facility, identify the membership of national health coverage, identify related community perceptions of health services at the primary level health facility, based on these two steps, then strategize implementation of optimization of national health Assurance Program through the enhancement and strengthen of primary health facilities services with the approach of the Gate Keeper in Managed Care in the framework of the attainment of Universal Health Coverage in Malang City. The design of this research is the combination of various research methods which include descriptif research, policy research and action research. Based on the research results, there are still some obstacles and constraints of Puskesmas as the first level health facilities : a) aspects of the service , b) aspects of human resources, c) aspects of management, d) aspects of facilities and infrastructure.